2020
DOI: 10.1097/ijg.0000000000001604
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Neuroretinal Rim Thickness and Visual Fields in Glaucoma: A Broken-stick Model

Abstract: I. Analysis of the structure-function relationship in the linear scale with the broken-stick model We also applied the broken-stick model to the VF data and the MDB structural parameters both in the linear scale. When the VF TD data was transformed to the linear scale, the observation that "the structurefunction relationship displayed a plateau, with neuroretinal rim thickness values being unrelated to VF values" was not readily visualized in some of quadrants/ sectors (Figure S1). Further statistical evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The segmented mixed effects regression model with P breakpoints φ 1 ,…, φ P can be written as where β = ( β 0 , β 1 , β 2 ) t corresponds to the intercept and random effects of x ijk , z ijk respectively, Ψ – ( β 1 , β 1 + ξ 1 ,…, β 1 + ξ 1 + ξ 2 +… + ξ P ) t are the P + 1 slopes (association effects) for each of the segments between P breakpoints. γ i ~ N (0,Σ γ ) and γ ′ ij ~ N (0,Σ γ ′ ) are the random effects for covariate S ij and S′ ijk .ε ijk ~ N (0, σ 2 ) are the independent individual errors. The model will shrink to the standard linear mixed-effects model when no breakpoint is detected (i.e., P = 0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmented mixed effects regression model with P breakpoints φ 1 ,…, φ P can be written as where β = ( β 0 , β 1 , β 2 ) t corresponds to the intercept and random effects of x ijk , z ijk respectively, Ψ – ( β 1 , β 1 + ξ 1 ,…, β 1 + ξ 1 + ξ 2 +… + ξ P ) t are the P + 1 slopes (association effects) for each of the segments between P breakpoints. γ i ~ N (0,Σ γ ) and γ ′ ij ~ N (0,Σ γ ′ ) are the random effects for covariate S ij and S′ ijk .ε ijk ~ N (0, σ 2 ) are the independent individual errors. The model will shrink to the standard linear mixed-effects model when no breakpoint is detected (i.e., P = 0).…”
Section: Methodsmentioning
confidence: 99%
“…An example for its use in ophthalmology is the association between structural and functional measurements in glaucoma. Numerous studies demonstrated varying level of association between structural measurements obtained by OCT, such as average retinal nerve fiber layer (RNFL) thickness, and functional measurements obtained with visual field tests, at different stages of disease severity [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly rapid progression of VF loss can subsequently be encountered as RNFL thinning plateaus. This asymmetric structure-then-function pattern of progression has been termed the ‘broken stick model’; Liu et al [38] found that detectible visual field loss began after the neuroretinal rim reached one-third normal thickness. Thus, a finding of OCT RNFL and/or macular progression should be noted and treated even in the absence of VF change, as such changes often predict future VF progression [39 ▪ ].…”
Section: Detecting Disease Progression In Moderate Glaucomamentioning
confidence: 99%